MATHEMATICAL MODEL OF A COLLISION BASED ON A SPRING-MASS-DAMPER SYSTEMWITH A NONLINEAR SPRING BEHAVIOR - Mereles, Arthur; Varanis, Marcus (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents a mathematical model of a collision were the phenomenon will be simplified by a spring-mass-damper model. The spring will be considered to have an elastoplastic behavior, which states that the spring suffers a permanent deformation after a force application. The responses of the model will be obtained analytically and by numerical approximation.The model proposed in this paper allows one to obtain parameters of the system, and then compare to a full-scale experiment to test its suitability with it. The nonlinear behavior of the system will be characterized by analyzing the phase space diagram.